The Development of the E-Student Worksheet Assisted with PhET Simulation on the Material of Momentum and Impulse for High School/Islamic High School Levels - Febrianti, Susi; Nengsih, Sri; Arusman (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2024)
The limited facilities in the laboratory are an obstacle for students in carrying out practicums. The material on momentum and impulse is considered complicated by students, this is due to the limited use of printed books as the only teaching material in the physics learning process. Therefore, it is necessary to use additional teaching materials in the form of E-Student Worksheet to help students understand the concepts of momentum and impulse. This research has two main objectives, namely to design an E-Student Worksheet design assisted by PhET Simulation and to determine the feasibility of the e-worksheet. Making E-Student Worksheet with the help of PhET Simulation is used as an interactive learning animation simulation to deepen understanding and increase students' interest in physics. The E-Student Worksheet development process assisted by PhET Simulation follows the model developed by Alessi and Trollip, which consists of three stages: (1) Planning, (2) Design, and (3) Development. The result of this research is E-Student Worksheet assisted by PhET Simulation which focuses on momentum and impulse material. Determining the suitability of the product is carried out through validation by media experts and material experts, with the percentage of media expert validation reaching 94.37%, and material expert validation reaching 93.14%. Based on these results, it can be concluded that E-Student Worksheet is very suitable for teaching material in the learning process.